2017
DOI: 10.1371/journal.pone.0169897
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling to Understand the Effect of Citrus Rootstocks on the Growth of ‘Shatangju’ Mandarin

Abstract: To obtain insight into potential mechanisms underlying the influence of rootstock on scion growth, we performed a comparative analysis of ‘Shatangju’ mandarin grafted onto 5 rootstocks: Fragrant orange (Citrus junons Sieb. ex. Tanaka), Red tangerine (Citrus reticulata Blanco), ‘Shatangju’ mandarin (Citrus reticulata Blanco), Rough lemon (Citrus jambhiri Lush) and Canton lemon (Citrus limonia Osbeck). The tree size of ‘Shatangju’ mandarin grafted onto Canton lemon and Rough lemon were the largest, followed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 81 publications
1
30
0
1
Order By: Relevance
“…This leads to the limited synthesis of GAs in the roots and to the decrease in their transfer to the above-ground part of the plant. That is the way the dwarf trees are formed (Liu et al, 2017). After applying exogenous GA3 to the apical parts of the shoots of dwarf form M. baccata, was observed a significant increase in the processes of growth of these shoots compared to those of the shoots without application of GA3 (Stolbikova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the limited synthesis of GAs in the roots and to the decrease in their transfer to the above-ground part of the plant. That is the way the dwarf trees are formed (Liu et al, 2017). After applying exogenous GA3 to the apical parts of the shoots of dwarf form M. baccata, was observed a significant increase in the processes of growth of these shoots compared to those of the shoots without application of GA3 (Stolbikova et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Citrus is very important worldwide for fruit production. Results of RNA-Seq data analysis in Citrus species showed that expression levels of ARF1, ARF8, GH3 and IAA4 genes were negatively correlated with the growth rate and the content of IAA hormone (Liu et al 2017b), indicating that expression of genes involved in auxin signal transduction may regulate the hormone levels. RNA-Seq data analysis between blight and healthy root samples identified mechanisms associated with blight phenotypes, starch accumulation, and abiotic stress (Zhang et al 2016).…”
Section: Citrusmentioning
confidence: 99%
“…Transcriptional profiling of the scions of Malus domestica revealed that differences in the expression of 116 transcripts were correlated with rootstock regulation of tree size in the scion [12]. In citrus, most differentially expressed genes (DEGs) of 'Shatangju' mandarin (Citrus reticulata Blanco) leaves were involved in the auxin signal transduction pathway and gibberellin (GA) biosynthesis pathway in grafted plants [13]. The whole-leaf transcriptome of a grapevine grafted onto five selected rootstocks showed high variability in gene expression, and 2692 DEGs and metabolites were involved primarily in defense responses (Chitarra [14].…”
Section: Introductionmentioning
confidence: 99%
“…The whole-leaf transcriptome of a grapevine grafted onto five selected rootstocks showed high variability in gene expression, and 2692 DEGs and metabolites were involved primarily in defense responses (Chitarra [14]. The tree size of the 'Shatangju' mandarin scion was found to be largest when grafted onto Canton lemon, and more than 1000 DEGs were found to be involved in the oxidoreductase function, hormonal signal transduction, and the glycolytic pathway in red tangerine vs. Canton lemon [13]. However, molecular regulation of the grafting effect on stem secondary growth has seldom been studied.…”
Section: Introductionmentioning
confidence: 99%